Two Views on Ukrainian Culture of the late 1910s-early 1920s in Two Open Letters from the Year 1960 - Maria Mayofis (eSamizdat)
In this article, I analyze two open letters published in 1960 in “Literaturnaia Gazeta”. In the first letter, Maksim Ryl’skii, a renowned Soviet Ukrainian poet and two-time winner of the Stalin Prize, accuses the famous writer (and his former friend) Konstantin Paustovskii of making unacceptable errors in describing Ukrainian culture of the late 19th-early 20th century in the third and fifth volumes of his memoirs, and Paustovskii answers him in a week in the same periodical. I propose reconstructing the key contexts that may explain the harsh polemic between these two former friends, pointing to the very different assessments of Ukrainian culture of the late 1910s and 1920s characteristic for both writers in the late 1950s, as well as to the hidden tensions within the Soviet writers’ milieu that made Paustovskii feeling particularly vulnerable.